Parastomal hernias and information retention: how and when to educate ostomates on risk minimisation. (2nd February 2022) - Vernon, Emma; Wright, Stephen; White, Pamela
Abstract : Background: Parastomal herniation is a common complication of stoma formation, caused by protrusion of the bowel through the abdominal wall, with a major negative impact on quality of life. Stoma care nurses should educate ostomates on how to minimise the risk of a parastomal hernia. However, new ostomates must absorb so much pre- and postoperative information that some of it may be missed, misunderstood or forgotten. Aims: A survey was conducted to determine how much information about parastomal hernias and risk minimisation patients remember, as well as the best way and time to deliver this information, including how often it should be repeated. Method: The survey comprised 13 multiple-choice questions and was distributed to adults with any type of stoma through medical equipment supplier SecuriCare Medical's postal mailing list and social media pages. These results were compared with findings from the literature. Findings: Of 544 participants, most were over 70 years old (55.2%) and had had a stoma for more than 10 years (59.1%). Of these, 70.6% had heard of parastomal hernias and 29.4% had not. Most of those who had heard of parastomal herniation heard of it when they were diagnosed with the complication (37.3%). Only 9.8% first heard of it from a stoma care nurse. Of those who had discussed herniation with a nurse, the largest group (26.4%) had done so at a postoperative home visit or clinic appointment. Conclusion: Those who have had their stoma for a long time are particularly likely to have never been educated on parastomal herniation or forgotten what they had learned, so are a priority for patient education. This education should be tailored to a patient's age, learning style and ability to process information in a short period, as well as anxiety level. Stoma care nurses should be careful to limit their use of jargon, abbreviations and the passive voice, as well as the amount and type of information being delivered. Such education should be delivered early and then repeated at regular intervals.